2017
DOI: 10.1111/bjd.15551
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors that may influence the selection of first‐line biological therapy for people with psoriasis: a prospective, multicentre cohort study

Abstract: This study offers important insights into the factors influencing current prescribing practice for first-line biological therapies for people with psoriasis. It provides baseline data to inform the evaluation of future potential changes that may affect prescribing behaviour, such as stratified medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
18
1
1
Order By: Relevance
“…Variability in treatment efficacy of adalimumab has been observed among these controlled and real-life studies, and causal factors have already been identified. 22,[28][29][30][31][32] While no difference was observed in terms of PASI response between biologic na€ ıve, previous anti-TNF-alpha or previous ustekinumab treatment on the effect of adalimumab, stepwise logistic regression in our study revealed that younger patients, no diabetes/metabolic syndrome, no dyslipidemia, no hypertension or a lower PASI at baseline were significantly associated with better achievement of PASI response by 3 and 6 months. Interestingly, at later time points (1, 2 and 3 years), absence of hypertension and a positive diagnosis for psoriasis/psoriatic arthritis were significantly associated with increased odds of achieving PASI 90 and complete remission (PASI 100).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Variability in treatment efficacy of adalimumab has been observed among these controlled and real-life studies, and causal factors have already been identified. 22,[28][29][30][31][32] While no difference was observed in terms of PASI response between biologic na€ ıve, previous anti-TNF-alpha or previous ustekinumab treatment on the effect of adalimumab, stepwise logistic regression in our study revealed that younger patients, no diabetes/metabolic syndrome, no dyslipidemia, no hypertension or a lower PASI at baseline were significantly associated with better achievement of PASI response by 3 and 6 months. Interestingly, at later time points (1, 2 and 3 years), absence of hypertension and a positive diagnosis for psoriasis/psoriatic arthritis were significantly associated with increased odds of achieving PASI 90 and complete remission (PASI 100).…”
Section: Discussioncontrasting
confidence: 63%
“…A higher proportion of psoriatic arthritis patients were observed in the anti‐TNF‐alpha group (62.9%) compared to biologic naïve (28.6%) and ustekinumab group (18.5%). This may be due to the fact that anti‐TNF‐alpha biologics have shown greater improvement in psoriatic arthritis patients compared to ustekinumab …”
Section: Discussionmentioning
confidence: 99%
“…We found evidence of such a change in treatment target in the adjusted analyses given that the HR for calendar year of treatment initiation was statistically significant (Table ). This effect may be important to account for in future effectiveness analyses, given recent observations of a general shift in prescribing strategy over time . Patients on ADA had lower mean PASI during maintenance treatment than patients on MTX (2.7 vs. 4.9).…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Davison et al . in the present issue of the British Journal of Dermatology identifies factors that influence dermatologists’ choice between adalimumab, etanercept and ustekinumab as a first‐line biologic therapy in patients included in the British Association of Dermatologists Biologic Interventions Register (BADBIR) between 2012 and 2015.…”
mentioning
confidence: 99%
“…3 in Davison et al .) . The analysis of factors determining the choice of biologic in second or subsequent courses of treatment is currently most relevant from a clinical perspective.…”
mentioning
confidence: 99%